Central Bank Digital Currency: Prospects and Applicability for E-Manat in Azerbaijan - Gambarov, Rufat; Aliyev, Ilgar; Hasanov, Tofig (ADA University, 2022)
The CBDCs have become one of the most talked about issues in the modern monetary policy circles. Standing for Central Bank Digital Currencies, CBDCs are the digital version of the fiat currency that is the collateral of the central banks and can be used to make transfers as well as the payments. The purpose of this paper is to look at the CBDC practices and come up with concrete and actionable recommendations for Azerbaijan to implement its own CBDC. The paper consists of the following parts: In the introduction, the major research aims and objectives as well as the research methodologies and the limitations of the research will be outlined to be followed by the literature review in which the existing literature will be dissected into several parts with the major arguments and opinions outlined. This will be followed by a comprehensive analysis of the CBDC and what it is and what it is not, in addition to its functional, technical, and operational aspects. A comprehensive analysis of the advantages and the disadvantages of the CBDCs will also be outlined to make a better case for the adoption of the CBDCs. In order to better illustrate the practical implications of the CBDCs and the success factors that determine the success of the project, the paper will provide a comparative cases study between Ecuador and the Bahamas, the countries that have experiences with the CBDC. The significant part of the paper will be dedicated to Azerbaijan and the financial digitalization in the country. This is important because the level of cash usage, the financial literacy and the adoption play some of the most important role in the determination of the success or the failure of the CBDCs projects. On the other hand, the paper will also assess the potential benefits of the CBDC for Azerbaijan including the efficiency in the payment systems, the financial inclusion and the possible monetary policy uses. On the other hand, the paper will also analyse and assess whether the country is ready to embrace the CBDC. Towards the end of the paper, there will be several recommendations for the country on how to prepare and roll out the CBDC. The paper will provide recommendations on five different and the related aspects of the CBDC including the conceptual recommendations, the design and the technical recommendations, the operational recommendations, the implementation recommendations, and the finally legal recommendations and will conclude with a concise and well-recapped conclusion.
Keywords: Central Bank -- Azerbaijan.; Digital Currency -- Azerbaijan.; E-Manat.; Business